A systematic review of immunomodulatory strategies used in skin-containing preclinical vascularized composite allotransplant models. Issue 2 (February 2022) - Kauke, Martin; Safi, Ali-Farid; Panayi, Adriana C.; Palmer, William Jackson; Haug, Valentin; Kollar, Branislav; Nelms, Laurel; Tchiloemba, Bianief; Pomahac, Bohdan
Summary: Background: Acute rejection remains a vexing problem in vascularized composite allotransplantation (VCA). Available immunosuppressive regimens are successful at minimizing alloimmune response and allowing VCA in humans. However, repeated rejection episodes are common, and systemic side effects of the current standard regimen (Tacrolimus, MMF, Prednisone) are dose limiting. Novel immunomodulatory approaches to improve allograft acceptance and minimize systemic toxicity are continuously explored in preclinical models. We aimed to systematically summarize past and current approaches to help guide future research in this complex field. Methods: We conducted a systematic review of manuscripts listed in the MEDLINE and PubMed databases. For inclusion, articles had to primarily investigate the effect of a therapeutic approach on prolonging the survival of a skin-containing preclinical VCA model. Non-VCA studies, human trials, anatomical and feasibility studies, and articles written in a language other than English were excluded. We followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Results: The search retrieved 980 articles of which 112 articles were ultimately included. The majority of investigations used a rat model. An orthotopic hind limb VCA model was used in 53% of the studies. Cell and drug-based approaches were investigated 58 and 52 times, respectively. We provide a comprehensive review of immunomodulatory strategies used in VCA preclinical research over a timeframe of 44 years. Conclusion: We identify a transition from anatomically non-specific to anatomical models mimicking clinical needs. As limb transplants have been most frequently performed, preclinical research focused on using the hind limb model. We also identify a transition from drug-based suppression therapies to cell-based immunomodulation strategies.